Three new polyketide derivatives of the endophytic fungus Aspergillus cristatus 2H1. Issue 8 (3rd August 2022) - Wu, Xue-Ming; Dai, Guan-Cheng; Zhou, Bei-Bei; Chen, Yong; Tan, Ren-Xiang
Abstract: Three new polyketide derivatives, 2-ethoxycarbonyl-endocrocin (1 ), 6-methoxy-2-ethoxycarbonyl-endocrocin (2 ) and pannorin C (3 ), along with sixteen known compounds (4–19 ) were isolated from a plant endophytic fungus Aspergillus cristatus 2H1. Their structures were elucidated by 1D/2D NMR and HR-ESI-MS data analysis. Compound 3 showed weak antibacterial activity against Staphylococcus aureus (MIC 20 μg/ml). Compounds 14 and 15 showed effective cytotoxicity on human melanoma A375 cells (IC50 4.13 μM for 14, 3.39 μM for 15 ). Graphical Abstract: UF0001